2020
DOI: 10.1101/2020.02.18.953851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription-associated topoisomerase activities control DNA-breaks production by G-quadruplex ligands

Abstract: G-quadruplexes (G4), non-canonical DNA structures, are involved in several essential processes. Stabilization of G4 structures by small compounds (G4 ligands) affects almost all DNA transactions, including telomere maintenance and genomic stability. Here, thanks to a powerful and unbiased genetic approach, we identify topoisomerase 2-alpha (TOP2A) as the main effector of cell cytotoxicity induced by CX5461, a G4 ligand currently undergoing phase I/II clinical trials. This approach also allowed to identify new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 93 publications
(119 reference statements)
1
14
0
Order By: Relevance
“…1c). 16,31,32 We have identified that TOP1 inhibition synergises with CX-5461 to inhibit HR-proficient HGSC cell proliferation, a critical finding supported by other studies demonstrating decreased survival upon treatment with pyridostatin in HeLa cells 32 or with CX-5461 in Eμ-Myc lymphoma 31 depleted of TOP1. Both TOP1 and TOP2 can localise to rDNA and are involved in regulating torsional stress during transcription and DNA replication.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…1c). 16,31,32 We have identified that TOP1 inhibition synergises with CX-5461 to inhibit HR-proficient HGSC cell proliferation, a critical finding supported by other studies demonstrating decreased survival upon treatment with pyridostatin in HeLa cells 32 or with CX-5461 in Eμ-Myc lymphoma 31 depleted of TOP1. Both TOP1 and TOP2 can localise to rDNA and are involved in regulating torsional stress during transcription and DNA replication.…”
Section: Discussionsupporting
confidence: 61%
“…44 In addition, G-quadruplex stabilisers such as pyridostatin can induce TOP2-dependent DNA DSBs that are countered by TOP1, likely through TOP1's ability to regulate negative supercoiling behind RNA Pol I. 32 With the combination of CX-5461 and the TOP1 inhibitor topotecan in HR-proficient HGSC cells, we found robust nucleolar recruitment of phosphorylated RPA (Ser33) and ATR. We previously found that CX-5461 enhances rDNA chromatin accessibility to MNase.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…3 DSBs can be generated directly, such as those generated by TOP2 poisoning, ionising radiation, or as a result of the conversion of a primary lesion or blocking structure by transcription or DNA replication. 91,92 DSBs are repaired by two principal mechanisms ( Fig. 3): the non-homologous end joining (NHEJ) pathway, which joins two DNA ends without a DNA template; and the homologous recombination (HR), in which nucleases strip away a stretch of nucleotides at broken ends, exposing a 3 0 overhang of ssDNA in a process called DNA end resection, then use the corresponding sister chromatid as a template to repair the damaged strand.…”
Section: The Dna Damage Response (Ddr)mentioning
confidence: 99%